INFORMATION AND DATA SERVICE COMPETENCE: CONCEPT, APPROACHES, AND SIGNIFICANCE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article focuses on explaining the concept of information and data service (IDS) competence, which is increasingly vital for future specialists. It addresses the content of IDS competence, various theoretical and practical approaches to this concept, as well as its significance in the digital age. By expanding upon the notion of IDS competence, the article clarifies its role in modern educational processes and professional activities.